2021
DOI: 10.1016/j.pbiomolbio.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Stages, scaffolds and strings in the spatial organisation of non-homologous end joining: Insights from X-ray diffraction and Cryo-EM

Abstract: Non-homologous end joining (NHEJ) is the preferred pathway for the repair of DNA double-strand breaks in humans. Here we describe three structural aspects of the repair pathway: stages, scaffolds and strings. We discuss the orchestration of DNA repair to guarantee robust and efficient NHEJ. We focus on structural studies over the past two decades, not only using X-ray diffraction, but also increasingly exploiting cryo-EM to investigate the macromolecular assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 135 publications
(232 reference statements)
0
5
0
Order By: Relevance
“…6), structure-guided drug discovery can exploit other specific pockets of DNA-PKcs in the development of allosteric inhibitors or proteolysis-targeting chimeric (PROTAC) drugs with enhanced potency and selectivity 31,32 . Degradation of DNA-PKcs eliminates not only its kinase activity but also the stage provided for downstream NHEJ and DNA damage response signalling 13,32,33 . However, PROTAC drugs cannot be guaranteed to be beneficial as previous studies have shown that inhibiting kinase activity has more potent effects than knockdown or knockout 34 .…”
Section: Articlementioning
confidence: 99%
“…6), structure-guided drug discovery can exploit other specific pockets of DNA-PKcs in the development of allosteric inhibitors or proteolysis-targeting chimeric (PROTAC) drugs with enhanced potency and selectivity 31,32 . Degradation of DNA-PKcs eliminates not only its kinase activity but also the stage provided for downstream NHEJ and DNA damage response signalling 13,32,33 . However, PROTAC drugs cannot be guaranteed to be beneficial as previous studies have shown that inhibiting kinase activity has more potent effects than knockdown or knockout 34 .…”
Section: Articlementioning
confidence: 99%
“…These authors also added Ku protein which is known to promote weak and transient interaction between DNA ends with rather short dwell time (Ramsden & Gellert, 1998). A pair of proteins XRCC4 and Lig4 are capable to form complex between two XRCC4 disordered tails and two Lig4 molecules attached to two tails of XRCC4 dimer (Liang et al, 2020;Wu, 2019). Each one of the two Lig4 molecules is capable to embrace tightly only one DNA duplex.…”
Section: Dna Repair Systemsmentioning
confidence: 99%
“…(3) Nucleases and polymerases participate in the processing of the DNA ends. 147 (4) The ligation of the processed DNA ends, performed by XLF, DNA ligase IV, and XRCC4 in NHEJ, 148 as shown in Figure 4 .…”
Section: Dna‐pkcs and Human Diseasesmentioning
confidence: 99%